PRODUCT PACKAGING ANALYSIS USING VIEW MODEL ON CONSUMER PURCHASING DECISION OF FRUIT FLAVORED DRINKS PRODUCT IN SURABAYA - Firmansyah, Muhammad Anang; Fatihudin, Didin (Sinergi : Jurnal Ilmiah Ilmu Manajemen, 2019)
Packaging is one way to promote a product, attracting consumers to buy a product. In order for the packaging to perform its functions properly, the model VIEW proposed by Terence A. VIEW here includes Visibility, Information, Emotional Appeal and Workability variables.The purpose of this research is first to analyze the influence of Visibility (X1), Information (X2), Emotional Appeal (X3) and Workability (X4) on consumer purchasing decision (Y) of Fruit Flavored Drinks product in SurabayaData obtained from 100 respondents who were sampled by filling questionnaire. Based on the analysis of multiple regretion known that the independent variables have a direct positive influence with the dependent variable. Furthermore the result of data analysis obtained value R2 equal to 0,71. This can be interpreted that 71% of variables dependent variables are influenced by independent variables. While the rest (29%) is influenced by other variables outside the model.Hypothesis test results both partial and simultaneous shows the analysis results that VIEW model consisting of variables Visibility (X1), Information (X2), Emotional Appeal (X3) and Workability (X4) have a significant influence both partially and simultaneously on consumer purchasing decision (Y) of Fruit Flavored Drinks product in Surabaya.Â Keywords: Product packaging VIEW Model, purchase decision.